Sophoricoside Alleviates Oxidative Stress and Inflammation in Streptozotocin-Induced Diabetes Mellitus in Rats - Yang, Jie; Yan, Lu; Zhang, Xinrong; Zhang, Jiawei (Indian Journal of Pharmaceutical Education and Research)
Background: Diabetes mellitus, a chronic metabolic condition defined by chronic hyperglycemia, presents a major global health challenge with increasing prevalence and profound implications for individual’s well-being and healthcare systems. Objectives: This work was aimed at studying the anti-diabetic properties of sophoricoside against Streptozotocin (STZ)-induced diabetes in rats. Materials and Methods: In this experimental model, diabetic condition was initiated in rats by injecting a single dosage of STZ (65 mg/kg). Following diabetes induction, the rats were treated orally with 50 mg/kg of sophoricoside for 8 weeks. After treatments, the effect of sophoricoside on the blood glucose and insulin level in the experimental rats was evaluated. The concentrations of creatinine, urea, lipid peroxidation and antioxidants, and inflammatory markers in the experimental rats were evaluated. Histological study was performed on the pancreas of experimental rats. Results: The findings of this work showed that sophoricoside considerably diminished blood glucose and augmented the insulin concentration in the diabetic rats. The sophoricoside also reduced the creatinine and urea concentrations in the diabetic rats. Additionally, the administration of sophoricoside effectively reduced inflammatory markers and alleviated oxidative stress by enhancing antioxidants. The findings of histological study of the pancreas further confirmed the salutary characteristics of sophoricoside. Conclusion: The findings of this work demonstrate that sophoricoside exerts beneficial activities in mitigating the diabetes in rats. These results recommend that sophoricoside may offer as a viable therapeutic option to treat diabetes.
Keywords: Hyperglycemia; Insulin; Sophoricoside; Pancreas; Streptozotocin; Oxidative stress.